Factors contributing to the experience of shame and shame management: Adverse childhood experiences, peer acceptance, and attachment styles. Issue 2 (4th March 2021) - Sedighimornani, Neda; Rimes, Katharine; Verplanken, Bas
ABSTRACT: Previous research has firmly established that some individuals experience shame more frequently than others. This study employed a cross-sectional design to explore factors that are related to the experience of shame. In this study, 240 participants completed self-reported assessments of parental care and expectations, maternal attitudes toward negative emotions, peer acceptance during childhood, attachment styles, and shame management. In particular, submissive shame management strategies (self-attack and withdrawal) and negative parental experiences were correlated with frequent experience of shame. In addition, a model was developed to depict the relationship between childhood experiences, attachment styles, shame, and shame management. The results suggest that negative parental experiences are contributory factors to the experience of shame, through attachment styles. The model illustrated how shame might be developed and how it might be managed.